Care coordination for people living with serious mental illness: understanding the caregiver's perspective - Pamela Obegu; Kayla Nicholls; Mary Alberti (Frontiers in Health Services)
IntroductionFamily caregivers of people living with serious mental illness such as bipolar disorder, psychosis and schizophrenia, are continuously burdened with caregiving, following the complexities of navigating the mental health system for their loved ones. The aim of the study was to understand the perspectives of caregivers about care coordination for people living with serious mental illness, highlighting the current landscape and new directions across Canada.MethodsIn this co-designed participatory qualitative research, caregivers of people living with serious mental illness, and service providers were engaged and purposively sampled across Canada.ResultsThe main findings of the study revealed care coordination as a key strategy to alleviate the burden of caregivers and enhance sustainable support for them. In complement with collaborative mental health care, care coordination can improve service delivery and strengthen the mental health system.ConclusionGiven the severity of bipolar disorder, psychosis and schizophrenia, it is important that we prioritize care for people living with these illnesses while providing support for their caregivers who bear the brunt of the otherwise fractured mental health system. Ultimately, collaboration between people and systems is how the mental health system can be much improved, and care coordinators serve as resourceful go-betweens in this ‘collaborativerse’.